Implementation of a Data Logging System for a Small Scale Hydrokinetic Turbine - Diana, Ringgau (Universiti Malaysia Sarawak (UNIMAS), 2020)
A suitable data logger is needed for data collection to demonstrate the practicality of Hydrokinetic Turbine (HKT) in a rural area of Sarawak application. HKT is a technology that extracts kinetic energy from river currents of almost zero elevation. Currently, commercial data loggers are embedded with features that may not be usable for specific applications of the system. Additionally, they use excessive amounts of energy and are incompatible with certain transducers. Conventionally, Turbem software has been used for the HKT’s numerical simulations. However, estimations of electrical power are usually higher than the experimental values obtained, which causes some difficulty in determining the right range of transducers. In this study, to cater to the problem, a prediction graph was produced by the combination of the BEM theory and laboratory experiments. The data logger was implemented with an automatic data-file creation capability, the energy consumption of which would be very low, and it would be easily customizable. Transducers such as a voltage divider showed 0.7% of error, and a current transducer performed at 5%. Whereas a propeller type current meter and rotational speed meter performed at 1% of inaccuracy. The data logger demonstrated an acceptable accuracy and behavior of the logging performance test. The real time operation of the data logger was also verified in a field test. The results showed that the terminal voltage suffered ±2% of error, while the output current, rotational speed of generator, river velocity and output power showed about ±4%, ±21%, ±16% and ±5% of error, respectively. Therefore, the ranges of the data logger’s transducers are considered within the HKT system nominal and operational values, except the range of the current transducer. These readings demonstrated that the data logger could fulfill its function.